ANALISIS MANAJEMEN KEWIRAUSAHAAN PADA USAHA BUDIDAYA IKAN NILA SERESO DI DESA KEDOTAN KECAMATAN SEKERNAN - muhammad khoirul Alfidoni; Arsa Arsa; Neneng Sudharyati (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze entrepreneurship in the Sereso tilapia fish farming business in Kedotan Village, Sekernan District, Muaro Jambi Regency, and identify the obstacles faced in its implementation. The approach used is qualitative research with descriptive methods. Data collection was carried out through in-depth interviews, field observations, and documentation. Informants were selected using a purposive sampling technique involving the business owner, feed manager, and six pond managers. The results show that entrepreneurial management in the tilapia fish farming business includes four main functions: planning, organizing, directing, and monitoring. Although most aspects have been running well, including the profit-sharing system, feed management, and CCTV monitoring, there are still weaknesses such as promises of written documentation, human resource limitations, and the absence of environmental impact reporting, which is part of the responsibility based on the Sharia Business Theory (SET). The main obstacles found include the owner's limited time and human resources, as well as technical problems with CCTV due to frequent power outages at the business location.